The Safety and Outcome of Minimally Invasive Staged Segmental Artery Coil Embolization (MIS2ACE) Prior Thoracoabdominal Aortic Aneurysm Repair: A Single-Center Study, Systematic Review, and Meta-Analysis - Dabravolskaite, Vaiva (MDPI, 2025)
Background: Minimally Invasive Staged Segmental Artery Coil Embolization (MIS(2)ACE) is a novel technique of spinal cord preconditioning used to reduce the risk of paraplegia in thoracoabdominal aortic aneurysm (TAAA) repair. In this study, we report our experience with MIS(2)ACE, including both degenerative and post-dissection TAAA, while we attempt to systematically summarize relevant data available in the literature. Design: single-center observational study with systematic review of the literature and meta-analysis.
Methods: Initial retrospective analysis of 7 patients undergoing MIS(2)ACE over 12 sessions with a subsequent systematic review of the literature and meta-analysis of the available published data (PROSPERO protocol number: CRD42023477411). Baseline patient and aneurysm characteristics, along with procedural technique and outcomes, were analyzed. One-arm pooling of proportions was used to summarize available published data.
Results: We treated seven patients (5 males, 71%) with a median age of 69 years (IQR 55,69). According to the Crawford classification, five patients (1%) had extent II TAAA, and two (29%) had extent III TAAA. Five patients (71%) had post-dissection -TAAA; four of them were after Stanford type A dissection, and one had a chronic type B dissection. Three patients (43%) had connective tissue disease. Of the seven patients, six (86%) underwent previous aortic surgery, while the median aneurysm diameter was 58 mm (IQR 55,58). MIS(2)ACE was successful in 11 sessions (92%). The median number of embolized arteries was 4 (IQR 1,4). There were no periprocedural complications in any embolization. The median embolization-operation time interval was 37.0 days (IQR 31,78). Two patients had open and five endovascular treatment. There were no events of spinal cord ischemia either after MIS(2)ACE or after the aortic repair. Out of the 432 initially retrieved articles, we included two studies in the meta-analysis, including patients with MIS(2)ACE for spinal cord preconditioning in addition to our cohort. The prevalence of pooled postoperative spinal cord ischemia among MIS(2)ACE patients is 1.9% (95% CI -0.028 to 0.066, p = 0.279; 3 studies; 81 patients, 127 coiling sessions).
Conclusions: While the current published data is limited, our study further confirms that MIS(2)ACE is a technically feasible and safe option for spinal cord preconditioning.